(untitled) (ACME, 2024)
In ancient Greek, compounds that have a noun formed with the suffix -σις as the second constituent are very rare and have little evidence: the majority, in fact, are represented by derivatives of already composed lexemes, especially verbs. Although the prototypical simple -σις nominal refer to events, the semantics of the non-derived -σις compounds is mostly resultative/instrumental, due to metonymic shift; this is confirmed by the syntactic behaviour of -σις compounds, closer to that of prototypical nouns, and therefore generally devoid of an argument structure. The second constituent of some -σις compounds does not occur in isolation, but the entire compound is still considered endocentric from a categorical point of view. The suffix -σις, poorly productive in composition, is replaced in this context by suffixes that fall within the thematic declension, in particular by -σία, replacing it instead in the creation of simple names, in a relationship similar to that which can be highlighted respectively, in the field of agent names, between the suffixes -τήρ/-τωρ and -της.